2020
DOI: 10.34117/bjdv6n4-374
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activity of olive trees cultivated in the Campanha Gaúcha region

Abstract: Antioxidant and antimicrobial activity of olive trees cultivated in the Campanha Gaúcha region Atividade antioxidante e antimicrobiana de folhas de oliveira cultivadas na Região da Campanha Gaúcha

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Several factors, such as olive cultivar, season and leaf drying process, influence the phenolic compound content in olive leaves (Nicolì et al ., 2019; Antunes et al ., 2020; Medfai et al ., 2020). Here, we studied the Rosignola cultivar and hypothesised that the composition of this cultivar might have a strong antioxidant and antimicrobial activity due to its phenolic composition but in a different amount.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors, such as olive cultivar, season and leaf drying process, influence the phenolic compound content in olive leaves (Nicolì et al ., 2019; Antunes et al ., 2020; Medfai et al ., 2020). Here, we studied the Rosignola cultivar and hypothesised that the composition of this cultivar might have a strong antioxidant and antimicrobial activity due to its phenolic composition but in a different amount.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, olive varieties affect microbial inhibition against E. coli and S . aureus (Antunes et al ., 2020). Thus, a difference in the MIC of extracts of olive leaves of the Frantoio variety was found against two mentioned bacteria (MIC of E. coli is 24 mg mL −1 , and S .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the olive leaf is the main source of several phenolic compounds, such as oleuropein, apigenin 7-O-glucoside, luteolin 7-O-glucoside, luteolin 4′-O-glucoside, and verbascoside [ 2 , 3 ]. Olive leaves are increasingly attractive for health benefits [ 4 ], due to their high natural biological activity, such as antioxidant, antimicrobial [ 5 ], anti-inflammatory [ 6 ], antidiabetic [ 7 ], and antiviral effects. Additionally, they may have favorable effects in protecting against chronic diseases, including cancer [ 3 , 4 , 5 , 6 , 7 , 8 ], cardiovascular, and neurodegenerative pathologies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of olive leaf extracts depends on many factors, such as the olive cultivar, extraction method (Soxhlet and microwaveassisted extraction, MAE), extraction time, and type of solvent. All these factors affect the total phenolic content, antioxidant activity, phenolic pro le of the extracts, and content of oleuropein, which is the predominant compound in all extracts [31,32]. OLE at a concentration of 62.5 mg/mL completely inhibited Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella enteritidis [33].…”
Section: Discussionmentioning
confidence: 99%